The Effect of 6 Weeks of Combination of Three Cone Exercise Using Ball and High-Intensity Interval Training on the Agility and Dribbling Ability of Student Futsal Athletes - Fajar Adi Wiranata; I Dewa Made Aryananda Wijaya Kusuma; Yanyong Phanpheng; Arif Bulqini; David Agus Prianto (Physical Education Theory and Methodology, 2023)
Study purpose. Three-Cone Drill using the Ball (TCDB) High-Intensity Interval Training (HIIT) is an exercise that requires players to perform fast movements and sharp changes of direction using a ball over three cones with high intensity. This exercise is based on the application of specific training principles using the ball and the principle of overload, which aims to improve agility and dribbling skills. This study aimed to evaluate the effect of TCDB+HIIT on the agility and dribbling ability of student futsal athletes.